Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan dengan Loyalitas Karyawan sebagai Variabel Intervening - Prabowo, Sony; Anindita, Rina; Wekadigunawan, C.S.P (Journal of Telenursing (JOTING), 2024)
This research analyzes the influence of job satisfaction and work motivation on team member performance and loyalty. The research method used is quantitative with a cross-sectional approach and path analysis research design. The research results show that the coefficient value of job satisfaction with performance is 0.545, which shows that the higher the job satisfaction, the more likely it is to improve performance. Then, the coefficient value of work motivation and performance is 0.239, which shows that the higher the work motivation, the more likely it is to improve performance. Then, the coefficient value of work loyalty with performance is 0.159, which shows that the higher the work loyalty, the more likely it is to improve performance. In conclusion, there is a positive influence between job satisfaction and team member motivation and performance. Keywords: Job Satisfaction, Performance, Loyalty, Motivation